Legal Transformation: Realizing Nomocracy and Transparency in the Field of Land Distribution in Indonesia - Isnin Harianti; Bayu Dwi Anggono; Fanny tanuwijaya (Publikasi Indonesia, 2024)
In Indonesia, the issue of land distribution is an important issue related to social justice and the legal system. The large number of agrarian conflicts and inequality of access to land shows the need for legal transformation to achieve the ideals of the rule of law (nomocracy) and transparency in land distribution. The purpose of this study is to analyze the legal transformation needed to realize the ideal of the rule of law (nomocracy) and transparency in the field of land distribution, focusing on efforts to ensure fairness in the land distribution system in Indonesia. This research uses Empirical methods. The research data was collected from literature published in reputable scientific journals. Literature is collected through searches in electronic literature databases, such as Google Schoolar and Scopus. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusions. The results show that the transformation of law in Indonesia towards nomocracy and transparency in land distribution aims to strengthen legal foundations, ensure justice, and reduce inequality of land access. The principle of nomocracy places law as the primary guide in decision-making, while transparency reduces the potential for corruption and land-related conflicts. Land law reform and land redistribution policies are crucial steps in achieving this goal. More open access to public information in the area of land distribution allows for greater public participation in decision-making processes. By strengthening transparency and the application of nomocracy principles, Indonesia can strengthen the foundation of its rule of law and ensure sustainability in land resource management.